Mengungkap Risiko Hepatitis B pada Ibu Hamil - Hasmi, Hasmi; Kole, Hervina; Medyati, Novita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to reveal the risk of Hepatitis B in pregnant women at the Waena Health Center, Jayapura City. The method used is a quantitative survey approach with a cross sectional design. The results showed that the age relationship was significant with the incidence of hepatitis B in pregnant women with a p value of 0.035. The length of marriage was found to have a p value of 0.521 or insignificant. The number of pairs, the results of the chi square analysis are known to have a p value of 0.000 or significant and parity is known to have a p value of 0.26 or not significant. Conclusion, the relationship between the number of sexual partners, age of marriage is significant with the incidence of Hepatitis B and the length of marriage and parity is not significant with Hepatitis B in pregnant women at the Waena Health Center, Jayapura City. It is necessary to educate pregnant women in order to prevent being infected with Hepatitis B. Keywords : Hepatitis B, Sexual Partner, Pregnant Women